The Role of English Proficiency in the Adaptation of Ukrainian Immigrant Children and Youth in Saskatchewan, Canada - Bryzh, Kateryna; Makarova, Veronika (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
This article reports the results of a small-scale study examining the role of English language proficiency in the adaptation of Ukrainian immigrant children and youth to life in Saskatchewan, Canada. The main objective of the study was to describe issues related to English as a Second Language (ESL) proficiency as they are perceived by Ukrainian children and youth and by their parents. The second objective of the study was to explore the following factors in the adaptation process: age, gender, duration of stay in Canada, age upon arrival in Canada, ESL class attendance, school type (English as the language of instruction or bilingual), and level of English proficiency. A total of 60 participants (30 children/youth and 30 parents) took part in the study. The methodology (mixed quantitative/qualitative) involved semi-structured interviews with the children/youth participants, an evaluation of their ESL proficiency, and a questionnaire survey of parents’ views on ESL-related adaptation difficulties experienced by children/youth. The results demonstrated that most Ukrainian immigrant children/youth reported that limited English proficiency was a major problem for them when they moved to Canada. The results of the study suggest that the difficulties experienced by a child who immigrates to Canada depend on the child’s ESL speaking proficiency, general ESL proficiency, duration of stay in Canada, and age upon arrival in Canada.